A simple and low-cost electrode based on Nafion-stabilized silver nanoparticles supported on FTO for the electrochemical determination of Pb (II) and Cu (II) - Leonardo J. Monroy-Cruz; Akemi Morales-Kato; Yndira Dolores-Maldonado; Katiuska Castro; Alen Zimic-Sheen; María Belén Balta; Geraldine J. Otayza-Melgarejo; Raúl León; Patricia Sheen; Wilner Valenzuela; Mirko Zimic (PLoS ONE, 2025)
Increasing awareness of the environmental risks posed by heavy metal accumulation in the environment—due to their toxicity and persistence in biological systems—has driven the development of more efficient and accessible detection methods. Conventional techniques, despite their accuracy, are often expensive, time-consuming, and reliant on non-portable specialized equipment. This study presents a novel, low-cost electrochemical sensor using a fluorine-doped tin oxide (FTO) electrode modified with Nafion-stabilized silver nanoparticles (AgNPs) for the rapid and accurate detection of Pb (II) and Cu (II) in water samples. The electrode preparation involved the ultrasonic cleaning of the FTO, followed by its surface modification with Nafion and the electrodeposition of AgNPs. Electrochemical and structural characterization confirmed the advantages of this approach, showing a significant improvement in conductivity and in the active surface area of the electrode, which allowed for the sensitive detection of the target metals. The optimization of analytical parameters, including accumulation time, deposition potential, and pH, facilitated the effective determination of the analytes by differential pulse anodic stripping voltammetry (DPV). The results demonstrated low detection limits of 8.87 ppb for Pb (II) and 3.26 ppb for Cu (II), suitable for in-situ applications in environmental monitoring according to environmental quality standards. The sensor’s portability, coupled with its low cost and rapid analysis capability, addresses critical challenges in current monitoring practices and opens new avenues for widespread environmental surveillance in remote areas such as the Andean regions, where heavy metal contamination is a significant concern.